KAJIAN EKONOMIS BUDIDAYA ANGGUR LAUT (Caulerpa spp.) DALAM BAK TERKONTROL POTENSIAL SEBAGAI GREEN GOLD PRODUK KELAUTAN INDONESIA - Dasep Hasbullah; Muhammad Ikhsan Wamnebo (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The macro market for sea grapes (Caulerpa sp) is huge and tends to increase. The large market potential and tendency to increase is expected to be not fulfilled by the supply of fishermen who harvest it from nature (the sea). Some people have tried to cultivate sea grapes, but so far the results have been unsatisfactory. The purpose of this study is to determine the growth and productivity of caulerpa cultivated in controlled media using spotcollectors and to determine the feasibility of caulerpa cultivation in controlled media. This research was conducted to respond to this challenge, namely through the study of cultivation in semi indoor hatchery, which is focused on experiments involving different maintenance media and planting containers (spotcollector). The goal is to get the best cultivation technology so that it can improve optimal production performance. During the test, the productivity of each treatment is measured, including absolute growth rate and specific growth, and at the end of the test, the level of business feasibility is measured. The results showed that the controlled tub with different spotcollectors produced an average daily growth of 16.34% with a multiple of production to the average planting weight of 4.37 times.